Analysis in organs at risk for gynecological radiotherapy by High Dose Rate Brachytherapy using Manchester point A, ICRU 38 Report and American Braquitherapy Society recomendation - Gustavo Piriz; Yolma Banguero; Alejandro De Rosa; Carlos Vega; Aldo Quarneti (Brazilian Journal of Radiation Sciences)
The gynecological treatment with High Dose Rate (HDR) Brachytherapy imply deliver dose to the tumor and spare the dose in organs at risk. In this work we apply the recommendations for prescribing dose given by the International Commission of Radiation Units (ICRU) reports 38, 89 and the American Brachytherapy Society (ABS). With both schemes of optimization, recommendation of ICRU 38 or ABS with vaginal point from ICRU 89. Were analyze the dose received by the organs at risk, in this case rectum and bladder and also the irradiated volume for patients that receive HDR brachytherapy treatment. An afterloading technique is applying with a Eckert & Ziegler MultiSource® equipment using a Co-60 source, 30 patients with 4 applications with cervical cancer are planning with HDR brachytherapy.